EFFECT OF MORDAN SYNTHESIS OF CANNED WASTE TO POWER IKAT DAN LAJU REMOVED METHYL VIOLET COLOR DYES BY FABRIC FIBER EFFECT OF MORDAN SYNTHESIS OF CANNED WASTE TO POWER - Jaslin Ikhsan; Endang Widjayanti LFX; Sunarto Sunarto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
This study aims to determine: the binding capacity of cloth toward methylene violet (MV) dye, the rate of releaseof methyl violet from cloth due to washing, and the effect of the addition of the mordant to the binding capacity and the rate of release. pH, temperature, and equilibrium time were always maintained in all experiments. Data of binding capacity were collected by isothem experiments and performed by measuring the concentration of methyl violet bound by cloth at various added-concentrations of methylene violet. Collected data were analyzed with a Langmuir and Freundlich isotherm equations. Data of release rate were collected by mesuring the concentration of free methylene violet dye in solution due to washing as a function of time. The release data were analyzed using the Lagergren rate equation. The analysis showed that bonding between methylene violet and cloth occurs with releasing protons and via hydrogen bonds. Binding capacity was represented by the Freundlich isotherm equation on which the capacity was decreased by the addition of mordant, with represented bythe constants of k 1 , 2.45 x 10 -8 and 1.75 x 10-8 M MV per gram of cloth, respectively. The addition of mordant also deceleratedoubly the releaseof MV from cloth due to washing whose constants k - 2 were 2103.039 and 1013.958 mmol g-1 min-1, respectively.